The Effect of Aerobic Endurance on Agility and Speed in Amateur Soccer Players - Turgut Kaplan; Maya Budak; Ömer Kahraman; İbrahim Halil Şahin (Selcuk University, 2023)
The aim of this study is to examine the effect of aerobic endurance on speed and agility performance in amateur soccer players. 18 male soccer players at the Türkiye regional amateur league voluntarily participated in the research. The mean age of the soccer players participating in the research; 24.61 ± 4.434 years, height; 181.50 ± 0.041 cm, mean body weight; 73.17 ± 6.364 kg, 30 meters mean speed; 4.663 ± 0.501 sec, pro-agility test means; Means of 5.713 ± 0.322 sec and VO2max; 44,163 ± 1.911 (ml/kg/min). In the study, the yo-yo test was used to determine VO2Max levels, the 30-meter sprint test to determine sprint performance, and the pro-agility test to determine agility performance. The results of this study was that high VO2max levels in soccer players had a significant effect on agility and speed performance. Additionally, when the effect size was examined, it was seen that VO2max level was more effective in speed performance than agility. Also, it was found that the VO2max level explained the speed performance by 37% and a 1-unit change in the VO2max level affected the speed by 0.16, while the VO2max level explained the agility performance by 40.2% and a 1-unit change in the VO2max level affected the agility performance by 0.11. In conclusion, It has been observed that aerobic endurance affects sprint performance more than agility. Considering the distances related to agility (18.28 m) and sprint test (30 m), it is thought that the effect level of aerobic endurance increases as the running distance increases. Therefore, aerobic endurance levels should also be considered when applying agility and speed exercises.